Navigating Cultural Bridges: Enhancing Intercultural Competence through Democratic Dialogue in Elementary Education - Winarsih, Sri; Bawawa, Marni; Anggawirya, Arin Mantara (Utamax : Journal of Ultimate Research and Trends in Education, 2024)
This study explores the unique approach of utilizing democratic dialogue to enhance intercultural competence and cultural literacy among elementary school students in Merauke Regency, addressing a critical gap in the literature on effective methodologies for fostering these competencies in young learners. The research employs a pre-experimental design with pre-test and post-test measurements involving 20 purposively sampled students, using a 21-item questionnaire to assess empathy, inclusion, and tolerance. Findings reveal significant increases in these competencies, with inclusion showing the highest improvement (1.5 points), followed by empathy and tolerance (each 1.3 points). The results underscore the effectiveness of democratic dialogue in creating a more inclusive and empathetic classroom environment by promoting openness and acceptance among students from diverse cultural backgrounds. However, the study acknowledges limitations, including the small sample size and lack of a control group, suggesting that further research with larger and more diverse samples is necessary to validate these findings. The implications of this study extend beyond the immediate educational context, proposing democratic dialogue as a powerful tool for cultivating global citizenship and empathy, thereby contributing to the broader goal of fostering intercultural understanding in an increasingly interconnected world.